PHÂN LẬP VÀ KHẢO SÁT TÌNH HÌNH KHÁNG KHÁNG SINH CỦA VI KHUẨN Escherichia coli SINH ĐỘC TỐ SHIGA PHÂN LẬP TẠI MỘT BẾP ĂN TẬP THỂ Ở KHU VỰC HÀ NỘI - Lê, Thị Lan Anh; Vũ, Thị Thương; Đinh, Thu Minh; Bùi, Thị Thanh Nga; Tạ, Thị Loan; Phạm, Thị Hà Giang; Phạm, Việt Hùng; Triệu, Phi Long (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ISOLATION AND INVESTIGATION OF ANTIBIOTIC RESISTANT OF SHIGA TOXIN PRODUCING Escherichia coli STRAINS IN A COLLECTIVE KITCHEN IN HANOI CITYE. coli contaminated food is increasingly common in Vietnam as well as in the world. In particular, the status of multi-drug resistant E. coli has been recognized and is of great concern globally. In this survey, we isolated 9 E. coli strains from food samples, surface of table samples and rectal swabs of kitchen staff at a collective kitchen in Hanoi city and examined the antibiotic resistant phenotype of 9 isolated E. coli strains on 24 common antibiotics. The results showed that only 1/9 strains were sensitive to 24 tested antibiotics, of which 8/9 strains were resistant to at least 2 antibiotics. 8/9 of strains were resistant to chloramphenicol and tetracycline, 7/9 strains were resistant to trimethoprim + sulfamethxazole, 5/9 strains were resistant to ampicillin, gentamycin, piperacillin, 4/9 isolates were resistant to cefuroxime, cefepime, cefotaxime and aztreonam. 3/9 strains resistant to cefazolin, tobramycin. 2/9 strains were resistant to ceftazidime and 1/9 isolates were resistant to amikacin and ciprofloxacin. 9/9 isolates were sensitive to amoxicillin/clavulanicacid, piperacillin/tazobactam, cefoxitin and carbapenem antibiotics such as ertapenem, imipenem and meropenem.